Implementation of a colorectal laparoscopic surgical program - short-term outcomes and conversion rates - Alves,Adriana Cherem (2013)
PURPOSE: although laparoscopic surgery for the treatment of colorectal diseases represents a major advance, it is currently performed in less than a third of patients undergoing colectomies. The aim of this study is to analyze the initial results of laparoscopic-assisted colorectal surgeries (LACS) performed in a department of Coloproctology in a tertiary hospital, as well as to study the impact of age, gender and body mass index (BMI) and use of ultrasonic scissors or vessel sealing devices in relation to conversion rate. METHODS: this is a prospective observational study with 215 patients who underwent LACS between January 2006 and June 2010 in the Department of Coloproctology at Felicio Rocho Hospital, Belo Horizonte. The data obtained from a specific electronic database included demographics, diagnosis, use of ultrasonic scissors or vessel sealing devices, reason for conversion, duration of hospitalization, lymph node harvest in cancer specimens, complications, and deaths. RESULTS: the laparoscopic-assisted approach corresponded to 36.4% of all colorectal surgeries performed during the study period. Most patients were female (74%), with a mean age of 53.2 years. Ultrasonic scissors or vessel sealing devices were used in 32% of LACS. Specimen extraction and anastomosis were performed through an auxiliary incision in most cases. The overall conversion rate was 12%, with a decrease of 47% after the first year. We did not observe any association between conversion rate and age, gender, BMI, and the use of ultrasonic scissors and vessel sealing devices. The average hospital stay was of 7.7 days and the overall rate of complications was 20%, including 10 anastomotic leaks (4.65%). The rate of postoperative mortality was 1.86%. CONCLUSIONS: despite the difficulties related to the learning curve and unavailability of ultrasonic scissors or vessel sealing devices in most cases, the implementation of LACS in our department can be considered successful in relation to short-term results and conversion rates.